Incapacitation Effects of Incarcerating Drug Offenders: Longitudinal Arrest Histories of Adults Arrested in Washington, DC, 1985-1986 - Cohen, Jacqueline ([Verlag nicht ermittelbar], 2000)
This study examined differences in criminal career parameters that determine the potential incapacitative effects of alternative sentencing policies directed at drug-involved offenders. In particular, the researchers explored three key aspects of offenders' criminal careers: participation, frequency of offending, and termination rates from active offending. The study focused on differences in levels of serious offending by drug-using and nonusing drug offenders compared to drug-using and nonusing predatory offenders. Longitudinal arrest data for a sample of arrestees were collected to characterize the offending patterns of drug-using and nonusing drug offenders and predatory offenders. The sample was drawn from adults arrested in Washington, DC, on any charge from July 1, 1985, to June 30, 1986. Data were collected from case files maintained by the Washington, DC, Pretrial Services Agency for 883 arrestees and 5,387 arrests. Previous and subsequent arrests of the same individual were linked to form an arrest history. Within the sample of arrestees, three main types of offenders were distinguished based on offense charge at target arrest: (1) drug offenders, (2) predatory offenders (persons charged with robbery or burglary), and (3) all others. This study focused on the first two groups and distinguished drug users from non-users based on the results of a urine drug screen administered following the target arrest. Variables regarding arrests include date of arrest, drug test result, charges filed, disposition date, disposition type, and sentence length imposed. Demographic variables include race, sex, and place of birth.